Patient Education in Inflammatory Bowel Disease: A Patient-Centred, Mixed Methodology Study. (23rd December 2017) - McDermott, Edel; Healy, Gerard; Mullen, Georgina; Keegan, Denise; Byrne, Kathryn; Guerandel, Allys; Forry, Mary; Moloney, Jenny; Doherty, Glen; Cullen, Gareth; Malone, Kevin; Mulcahy, Hugh
Abstract: Background: Consensus guidelines from the European Crohns and Colitis Organisation conclude that optimizing quality of care in inflammatory bowel disease [IBD] involves information and education. However, there is no standardized patient education programme in IBD and education varies from centre to centre. Aim: To assess patients' education needs in IBD to facilitate design of a patient education programme. Methods: We created focus groups of 12 patients with IBD and used qualitative analysis to generate hypotheses. We then developed a quantitative questionnaire which was disseminated to 327 IBD patients attending three different centres. Five patients declined to participate and thus 322 patients (159 [49%] male, 180 [58%] Crohn's disease, median age 38 years and disease duration 7 years) were included. Results: Patients were most keen to receive education on medications, 'what to expect in future', living with IBD and diet. They wanted to receive this information from specialist doctors or nurses and believed it could improve their quality of life. Though the internet was the preferred source of general information [i.e. planning holidays], it was the least preferred source of IBD education. While there was a trend for females to prefer peer education, family history of IBD was the only statistically significant factor associated with information preferences. Conclusion: This is a patient-centred, mixed methodology study on patient education in IBD. Patients' preferences for education include components such as what to expect and diet and patients seem to distrust the internet as an IBD information source. International validation would be valuable to create a consensus education programme.